KAJIAN YURIDIS HAK KEPERRDATAAN BAGI ANAK-ANAK TERLANTAR - Ni Putu Juniasti; Any Suryani Hamzah (Fakultas Hukum Universitas Mataram, 2021)
This study has purposed to analyze the development of legal protection and state legal responsibility against homeless child private rights.The research method on this study uses normative or doctrinal legal research. The normative or doctrinal legal research is research to give a systematical explanation to legislation, the hard to implement and the prediction the legislation on the future. Based on this research, the result of this study showed that the lack of the state legal responsibility realization against the homeless child in the government operational because the government is not implemented good governmentprinciple in their systems.Furthermore, there is no strong political will from the government to take care of the homeless child.In this research, there are obstacle factors on the legal protection to the homeless child in Indonesia such asthe legal enforcement itself, this is relatedto the ability of legal enforcement officials, supporting facilities, and infrastructure, the government plan is not yet all effective implemented, because the different economic people in Indonesia mostly they have low income.